2020
DOI: 10.1089/nat.2020.0847
|View full text |Cite
|
Sign up to set email alerts
|

Likelihood of Nonspecific Activity of Gapmer Antisense Oligonucleotides Is Associated with Relative Hybridization Free Energy

Abstract: Reduction of matched and nearly complementary unintended transcripts was evaluated for 96 antisense oligonucleotides (ASOs) and 832 nearly matched unintended transcripts. The ASOs were 16-20 nucleotide ''gapmers'' with a gap of 8-10 DNA residues and 2¢-O-methoxy-ethyl or constrained-ethyl substitutions in the wings. Most unintended transcripts were not reduced or were reduced with a potency more than 10-fold weaker than the intended transcript. For the unintended transcripts that were reduced, a strong correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 63 publications
0
19
0
Order By: Relevance
“…However, modified DNA is generally used as ASO drugs to improve bio-stability and cellular uptake of the oligonucleotides. The stability of hybridization with ASO is reported higher than that with unmodified DNA ( 68 , 69 ). Therefore, truncated ASO with a much shorter length than the sgRNA can be used to obtain optimal binding affinity.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…However, modified DNA is generally used as ASO drugs to improve bio-stability and cellular uptake of the oligonucleotides. The stability of hybridization with ASO is reported higher than that with unmodified DNA ( 68 , 69 ). Therefore, truncated ASO with a much shorter length than the sgRNA can be used to obtain optimal binding affinity.…”
Section: Resultsmentioning
confidence: 92%
“…Therefore, truncated ASO with a much shorter length than the sgRNA can be used to obtain optimal binding affinity. A recent report clearly suggested that duplex stability of modified ASO can be correlated with the stability of unmodified duplex in 100 mM NaCl solution ( 68 ). The stability changes of hybrid duplexes in physiological salt concentration resulting from replacing DNA with different kinds of chemically-modified ASO were published earlier ( 68 , 69 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the interaction between the nucleic acids and proteins, including polymerase, must be considered to more precisely understand the reaction. The parameters can also be beneficial in antisense oligonucleotide (ASO) technology for selecting effective DNA oligonucleotides in crowded environments because a recent report showed that NN parameters are also suitable predictor for chemically modified ASO/RNA duplexes (46).…”
Section: Resultsmentioning
confidence: 99%
“…They calculated the edit distance, a count of the number of mismatches or gaps between the ASO and RNA sequence, to all genes, and found that 139 / 256 (54%) of all downregulated genes were at an edit distance of zero or one. Others have used qPCR dose-response experiments to investigate off-targets nominated from in silico screens of 96 high viability gapmers (Watt et al, 2020). In this study 97/ 832 predicted off-target sites had a reduction in gene expression with potency within 10-fold of the intended target transcript.…”
Section: Introductionmentioning
confidence: 99%